Raport mniejszosci - Dick, Philip K. (Warszawa : Amber, 2002)
Polish translation of "Minority Report". Washington D.C. has been murder-free thanks to new technology which identifies killers before they commit their crimes. But when the chief of Pre-Crime unit is himself accused of a future murder he has just 36 hours to uncover who set him up.
Translation of: The minority report.
Keywords: Crime prevention -- Fiction